Representation of Longing and Waiting for Lover in the Lyrics of Saalulinnas Song by Mansour Rahbani (Semiotic Analysis of Ferdinand de Saussure) - Umam, Ahmad Zaimul; Anjaswara, Bening; Sopian, Asep (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
Arabic song lyrics are a form of literary work that contains beauty and depth of meaning. This study aims to reveal the forms of longing and waiting for lovers through the main concept of Ferdinand De Saussure's semiotic theory of sign systematics, which includes signifiers and signified in the lyrics of Saalulinnas song by Mansour Rahbani. This research uses a descriptive qualitative research method with a content analysis design in the form of Arabic song lyrics. Data collection techniques used were reading, note-taking, and translation. The data analysis technique uses steps, namely collecting data, reducing data, presenting data, and drawing conclusions. This study found that the song lyrics with the title Saalulinnas by Mansour Rahbani have eight core stanzas; of the eight stanzas, there are 16 signifiers and 16 signs that represent forms of longing and waiting for lovers between Fairuz and Assi consisting of 8 forms, namely: abandonment, hard day, faith, secret, separation, dream meeting, heart guide, and suffering. The conclusion of this research shows that in the lyrics of the Arabic song entitled Saalulinnas by Mansour Rahbani, there are forms of longing and waiting for lovers.